The comparison between artificial turf and natural grass on speed and agility performance among amateur football players / Mohd Nazrul Azman Ramli - Ramli, Mohd Nazrul Azman (Faculty of Sport Sciences and Recreation, 2020)
The purpose of this study was to investigate the comparison two different surfaces which are artificial turf and natural grass on speed and agility performance among amateur football players of team Goyang FC, Kuantan. The total of 25 amateur players from team Goyang FC, Kuantan (n=25) were selected as the sample of the study using purposive sampling technique and will test in two different surfaces (artificial turf and natural grass). The component of speed and agility were measured using 30 Meter Sprint Test and Illinois Agility Test. Statistical analysis of the tests was conducted by using paired sample t-test. A set of data was recorded and been analyze. There was a significant different for the artificial turf and natural grass on speed and agility test. Hence, it was concluded that artificial turf and natural grass show a difference on speed and agility of the players.